Revisão dos casos de Odontoma, Fibro-Odontoma Ameloblástico e Fibro-Dentinoma Ameloblástico: estudo interinstitucional brasileiro - Ávila, Natália Goncalves Amaral (2023)
Ameloblastic Fibroma (AF), Ameloblastic Fibro-Odontoma (FOA), Ameloblastic FibroDentinema (FDA) and Odontoma (OD) were classified as distinct entities until the 3rd edition of the WHO (2005). In 2017, the 4th edition excluded the FOA/FDA, and considered these entities as stages of maturation of an OD. However, some authors believe that part of FOA and FDA are distinct entities and should be classified as neoplasms and not part of the maturation of an OD, due to some clinical and morphological characteristics that may be different, and the biological behavior that is often aggressive. This work reviewed the cases diagnosed as FOA/FDA, Composite OD, Complex OD and Developmental OD in 3 reference anatomopathology services in Brazil (UFES, UFPE, UEPB) from 2001 to 2023. Based on clinical and morphological criteria currently reviewed and described in the literature, these cases were reclassified and characterized, according to their sociodemographic and clinicopathological aspects. There was 1 case of FOA/FDA in the initial sample, which after review was reclassified as Developing OD. 98 odontomas were identified, 76.5% Compound OD (n=75), 21.4% Complex OD (n=21) and 2.1% Developing OD (n=2). Regarding sociodemographic aspects, the majority of injuries affected young patients with black skin color, without predilection for sex, with signs/symptoms that were mostly infrequent. The most affected location was the anterior maxilla in Compound OD and posterior mandible in Complex OD and Developmental OD. Most lesions were up to 3 cm in size and eruption disorders were associated with odontomas. Radiographic aspects were essential for the correct diagnosis of odontomas and therefore the clinical hypotheses were in accordance with the final diagnosis. Cords and small islands of odontogenic epithelium, fibrous/loose connective tissue, enamel, dentin, cementum and tissue compatible with dental pulp were morphological features commonly found, while ghost and granular cells were infrequent. Few cases of odontomas were associated with developmental odontogenic cysts. FOA/FDA is a rare lesion and multicenter studies are necessary to better characterize and understand this pathology. This work presents a characterization of a representative sample of OD, being the first study that describes its detailed morphological aspects.